Effect of spent coffee grounds and Stenotrophomonas rhizophila SRCM 116907 on the removal of ammonia and sulfur compounds in cattle manure - Kim, Jinwon; Ryu, Myeong-Seon; Park, Young Kyoung; Seo, Ji-Won; Lee, Ranhee; Yang, Hee-Jong; Jeong, Do-Youn (Journal of Animal Environmental Science, 2024)
The purpose of this study is to develop technology to reduce odors in livestock facilities by using spent coffee grounds (SCGs) and Stenotrophomonas rhizophila SRCM 116907 to target the primary sources of odors, namely ammonia nitrogen and hydrogen sulfide emissions. The efficacy and mechanisms of SCGs in removing odorous substances are investigated, and microorganisms with organic decomposition and odor reduction capabilities are also selected. Furthermore, the application of SCGs in real settings is analyzed using Next-Generation Sequencing (NGS). The results showing the chemical properties of cattle manure revealed that ammonia and hydrogen sulfur compound are the main odor causes. Treatment of cattle manure 10 wt% SCGs + S. rhizophila SRCM 116907 resulted in significant reductions of approximately 68.7% in NH3-N and 49.6% in H2S, respectively. This study investigates the removal efficiency and mechanisms of odor-inducing substances using SCGs and S. rhizophila SRCM 116907. Promising results in enhancing ammonia removal were demonstrated with S. rhizophila SRCM 116907. KCI Citation Count: 0